2016
DOI: 10.1097/hco.0000000000000275
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis in heart failure

Abstract: Current and future acquisition of accurate, unbiased, and comprehensive transcriptome data will continue to inform the understanding of heart failure, enabling hypothesis testing as well as hypothesis generation. Transcriptome data represent a vital bridge between genomic and epigenomic variation and proteomic output; progressive integration of data from these and other domains will fully realize the potential inherent in transcriptome analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…In the past two decades, global transcriptome analysis by microarray or RNA-seq has been greatly applied not only to explore the molecular mechanism underlying the pathogenesis of ischemic heart diseases but also to identify biomarkers useful for diagnostic, prognostic, and therapeutic purposes. Numerous genes have been recognized as causative or responsive factors in the repair and remodeling of the infarcted heart [32][33][34]. However, few studies have revealed their temporal changes after MI [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…In the past two decades, global transcriptome analysis by microarray or RNA-seq has been greatly applied not only to explore the molecular mechanism underlying the pathogenesis of ischemic heart diseases but also to identify biomarkers useful for diagnostic, prognostic, and therapeutic purposes. Numerous genes have been recognized as causative or responsive factors in the repair and remodeling of the infarcted heart [32][33][34]. However, few studies have revealed their temporal changes after MI [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…However, the predictive value of the RNA signature requires elucidation in large clinical trials. 62 However, metabolomic and lipidomic phenotyping of patients having HFrEF/HFpEF to indicate a profile of oxidative stress, lactic acidosis, and metabolic syndrome, coupled with mitochondria dysfunction, is a promising approach to stratify them at high risk of poor outcomes. 63…”
Section: Prospectivesmentioning
confidence: 99%
“…Transcriptome analysis in large animal model of HF is widely used in HF research ( 6 , 7 ). In recent years, transcript data in HF model have been analyzed by the next-generation sequencing (NGS) or Affymetrix exon arrays (Santa Clara, CA, USA), such as prediction of alternative splicing (AS) events and lncRNAs ( 8 , 9 ). However, these techniques had limitations in recognizing AS isoforms, homologous gene families, and complete and accurate assembly of transcripts because of short read data.…”
Section: Introductionmentioning
confidence: 99%